2023
DOI: 10.1007/s13399-023-03822-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of torrefaction on the biochar characteristics produced from sesame stalks and bean husk

Abstract: Torrefaction encourages homogeneity and enhances the energy-producing capabilities of biomass. In the current study, bean husk (BH) and sesame stalks (SS) were torrefied for 30 and 60 min at operating temperatures of 200, 225, 250 and 275, and 300 °C with nitrogen purging. Mass yield (MY), higher heating value (HHV), energy yields (EY), and torrefaction severity index (TSI) were examined. The variations of the biochar characteristics, pyrolysis kinetics by applying two models (Coats and Redfern (CR) and Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
(147 reference statements)
0
0
0
Order By: Relevance
“…It is confirmed that the highest temperature and residence time of the torrefaction method for sesame stalk biochar production (generated from 200 to 300 °C for 30 and 60 min) produced the highest carbon mass fraction (55.77%) and fixed carbon (55.10%). On the other hand, biochar yield, oxygen content, and hydrogen content declined to their lowest values with increasing temperatures, resulting in decreased H/C and O/C molar ratios due to the decay of hemicellulosic and cellulosic compounds (Khairy et al 2023). Park et al (2015) detected a similar observation by studying the effect of pyrolysis temperature on the sesame biochar characteristics and its phosphorus release.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is confirmed that the highest temperature and residence time of the torrefaction method for sesame stalk biochar production (generated from 200 to 300 °C for 30 and 60 min) produced the highest carbon mass fraction (55.77%) and fixed carbon (55.10%). On the other hand, biochar yield, oxygen content, and hydrogen content declined to their lowest values with increasing temperatures, resulting in decreased H/C and O/C molar ratios due to the decay of hemicellulosic and cellulosic compounds (Khairy et al 2023). Park et al (2015) detected a similar observation by studying the effect of pyrolysis temperature on the sesame biochar characteristics and its phosphorus release.…”
Section: Introductionmentioning
confidence: 69%
“…The moisture content of SS was relatively low, less than 10%. This percentage is favorable for the pyrolysis process (Khairy et al 2023). However, the moisture contents of both T1 and T2 were relatively close and lower than SS by about 50%.…”
Section: Sesame Stalk Feedstock and Biochar Characterizationmentioning
confidence: 96%
“…Biochar O/C -0.12; Biochar H/C -0.66; HHV-25.73 MJ kg -1 ; Energy yield -47.52%; Fuel Ratio -5.87; Thermal stability -0.85.Biochar O/C -0.64; Biochar H/C -1.25; HHV-20.5 MJ kg -1 ; Biochar yield -76.25%; Fuel Ratio -0.52;[119] …”
mentioning
confidence: 99%